(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The Liberal Mexican Party (PLM) was an organization which at the beginning adopted radical, liberal ideas, but later it became anarchist – communist. Its preeminence took place between 1900 and 1930, at the same time that many important societies lived similar problems caused by the radicalism. The article emphasizes the relations the PLM had with other countries beyond the border. It analyzes how not only did the “magonistas” (Ricardo Flores Magón’s supporters) know about politicians and political dynamics in the United States and Mexico, but they also knew that any transformation of the society in Mexico depended on the changes in the USA. Furthermore, this transformation should be worldwide, a world social revolution that ought to be actively driven by individuals. That is why they planned to become activists beyond the borders, this is internationally.